Does Severity of Alzheimer's Disease Contribute to Its Responsiveness to Modifying Gut Microbiota? A Double Blind Clinical Trial - Agahi, Azadeh; Hamidi, Gholam Ali; Daneshvar, Reza; Hamdieh, Mostafa; Soheili, Masoud; Alinaghipour, Azam; Esmaeili Taba, Seyyed Mohammad; Salami, Mahmoud (Frontiers in Neurology, 2018)
Alzheimer's disease (AD) is associated with cognitive dysfunction. Evidence indicates that gut microbiota is altered in the AD and, hence, modifying the gut flora may affect the disease. In the previous clinical research we evaluated the effect of a probiotic combination on the cognitive abilities of AD patients. Since, in addition to pathological disorders, the AD is associated with changes in oxidant/anti-oxidant and inflammatory/anti-inflammatory biomarkers, the present work was designed to evaluate responsiveness of the inflammatory and oxidative biomarkers to the probiotic treatment. The control (CON) and probiotic (PRO) AD patients were treated 3 months by the placebo and probiotic supplementation, respectively. The patients were cognitively assessed by Test Your Memory (TYM=50 scores). Also serum concentrations of nitric oxide (NO), glutathione (GSH), total antioxidant capacity (TAC), malondialdehyde (MDA), 8-hydroxy-2' -deoxyguanosine (8-OHdG) and cytokines (TNF-a, IL-6 and IL-10) were measured. The cognitive test and the serum biomarkers were assessed pre- and post-treatment. According to TYM test 83.5% of the patients showed severe AD. The CON (12.86%±8.33) and PRO (-9.35%±16.83) groups not differently scored the cognitive. Not pronounced change percent was found in the serum level of TNF-α (1.67%±1.33 vs. -0.15%±0.27), IL-6 (0.35%±0.17 vs. 2.18%±0.15) and IL-10 (0.05%±0.10 vs. -0.70%±0.73), TAC (0.07%±0.07 and -0.06%±0.03), GSH (0.08%±0.05 and 0.04%±0.03), NO (0.11%±0.06 and 0.05%±0.09), MDA (-0.11%±0.03 and -0.17%±0.03) and 8-OHdG (43.25%±3.01 and 42.70%±3.27) in the CON and PRO groups, respectively. We concluded that the cognitive and biochemical indications in the patients with severe AD are insensitive to the probiotic supplementation. Therefore, in addition to formulation and dosage of probiotic bacteria, severity of disease and time of administration deeply affects results of treatment.